PERAN ARBITRASE INTERNASIONAL DALAM PENYELESAIAN SENGKETA INVESTASI: IMPLIKASI BAGI INDONESIA: Peran Arbitrase Internasional dalam Penyelesaian Sengketa Investasi: Implikasinya Terhadap Indonesia - Adji Arya Pratama, Adji; Dani Widiyanti, Ikarini; Puspitho Andhini, Pratiwi (UIR Press, 2025)
International arbitration has become the primary mechanism for resolving cross-border investment disputes, particularly those involving foreign investors and host states. In the era of economic globalization, this mechanism is considered more efficient, neutral, and capable of providing legal certainty compared to domestic litigation. For Indonesia, the role of international arbitration carries dual implications. On one hand, it enhances the country’s attractiveness to foreign investors by ensuring legal protection for their investments. On the other hand, it poses challenges in the form of potential claims that may lead to financial burdens and affect the nation’s reputation in the international arena. Thus, the role of international arbitration in investment disputes extends beyond case settlement, encompassing legal policy, state sovereignty, and economic development strategies. This study highlights the importance of maintaining a balance between investor protection and national interests, while underlining the need for Indonesia’s investment law reforms to better adapt to the dynamics of international dispute resolution.